NMR solution structure of a DNA dodecamer containing a transplatin interstrand GN7-CN3 cross-link. - Paquet, F (1999)
The DNA duplex d(CTCTCG*AGTCTC).d(GAGAC-TC*GAGAG) containing a single trans- diammine-dichloroplatinum(II) interstrand cross-link (where G* and C* represent the platinated bases) has been studied by two-dimensional NMR. All the exchangeable and non-exchangeable proton resonance lines were assigned (except H5'/H5") and the NOE intensities were transformed into distances via the RELAZ program. By combining the NOESY and COSY data (330 constraints) and NMR-constrained molecular mechanics using JUMNA, a solution structure of the cross-linked duplex has been determined. The duplex is distorted over two base pairs on each side of the interstrand cross-link and exhibits a slight bending of its axis ( approximately 20 degrees ) towards the minor groove. The platinated guanine G* adopts a syn conformation. The rotation results in a Hoogsteen-type pairing between the complementary G(6)* and C(19)* residues which is mediated by the platinum moiety and is stabilized by a hydrogen bond between O6(G(6)*) and N4H(C(19)*). The rise between the cross-linked residues and the adjacent residues is increased owing to the interaction between these adjacent residues and the ammine groups of the platinum moiety. These results are discussed in relation to the slow rate of closure of the monofunctional adducts into interstrand cross-links.